2020
DOI: 10.1002/ajb2.1573
|View full text |Cite
|
Sign up to set email alerts
|

Plant response to fungal root endophytes varies by host genotype in the foundation species Spartina alterniflora

Abstract: Plants and their interactions with root-associated fungi have wide-reaching ecological effects, from influencing individual traits to modifying interactions with other species to affecting biodiversity and biogeochemical cycles (Johnson et al., 2012). While mycorrhizal fungi have long been of interest, there is growing evidence that other root-associated fungi markedly influence host plant structural and physiological traits, particularly when mycorrhizal fungi are absent or in low abundance (Porras-Alfaro and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 53 publications
1
7
0
Order By: Relevance
“…The presence of melanized, septate hyphae and microsclerotia were used as indicators of DSE and quantified using the grid-line intersect method (McGonigle et al, 1990) using ~100 intersections per sample. Root samples were not stained as melanized hyphae were clearly visible without this step as observed in other study systems (Liu et al, 2017;Hughes et al, 2020). The remaining fine roots were stored at −20°C until molecular analysis of fungal communities.…”
Section: Experimental Methods and Samplingmentioning
confidence: 99%
“…The presence of melanized, septate hyphae and microsclerotia were used as indicators of DSE and quantified using the grid-line intersect method (McGonigle et al, 1990) using ~100 intersections per sample. Root samples were not stained as melanized hyphae were clearly visible without this step as observed in other study systems (Liu et al, 2017;Hughes et al, 2020). The remaining fine roots were stored at −20°C until molecular analysis of fungal communities.…”
Section: Experimental Methods and Samplingmentioning
confidence: 99%
“…Unlike P. atricolor , most of them are relatively easy to culture so they could be used in resynthesis experiments to reveal their actual colonization pattern, possibly with a model non-seagrass hosts, since many endophytes do not seem to be host specific. However, the experimental results available to date indicate negative effects of lulworthioid fungi on their host plants (Hughes et al . 2020).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we know very little about the interactions with the microbiome in the species, but microbes have been highlighted as important symbionts in these and other challenging environments (Bowen et al, 2017; Angermeyer et al, 2018; Jung et al, 2021). Soil microbial activity could have dramatic impacts on the future nutrient availability and stability of these coastal sediments (Deegan et al, 2012; Bowen et al, 2017; Hughes et al, 2020; Lewis et al, 2021). In fact, a recent study suggested that bacterial community composition differed among R. mangle maternal genotypes but not with genetic diversity (Craig et al, 2020).…”
Section: Discussionmentioning
confidence: 99%